Study of anticoagulant activity of Yerba Mate and Yerba Mate with Ginger in vitro - سعيد كارول; الدياب ديمة; حسن نعمى (Latakia University Journal -Medical Sciences Series, 2024)
Yerba mate (YM) is a popular tea that is consumed in large quantities in our country, alone or with some herbal like ginger. It is prepared by infusion of the dried leaves of Ilex Paraguariensis in hot water. Although, it is a rich source of active compounds, such as polyphenol compounds which have been proven to have anticoagulant activity in many research, but the anticoagulant activity of YM has not been studied yet. This study aimed to investigate the anticoagulant activity of YM alone and with ginger by testing its effect in vitro on prothrombin time (PT) using plasma from healthy adults. Different concentrations of YM and YM with ginger were prepared and the total phenolic content was determined using the Folin-Ciocalteu method. The results showed that the phenolic content of 1g YM and 1g of the mixture with ginger were (90.457 mgGAE/g) (106.88 mgGAE/g) respectively. In-vitro PT test showed that Both YM and YM with ginger can prolong prothrombin time.